Talking Appalachian : voice, Identity, And Community - Clark, Amy (Amy D.); Hayward, Nancy M., 1945- (University Press of Kentucky, 2013)
Tradition, community, and pride are fundamental aspects of the history of Appalachia, and the language of the region is a living testament to its rich heritage. Despite the persistence of unflattering stereotypes and cultural discrimination associated with their style of speech, Appalachians have organized to preserve regional dialects -- complex forms of English peppered with words, phrases, and pronunciations unique to the area and its people. Talking Appalachian examines these distinctive speech varieties and emphasizes their role in expressing local history and promoting a shared identi.